2020
DOI: 10.1007/s10157-020-01930-8
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus vaccination in children with nephrotic syndrome: insignificant risk of relapse

Abstract: Background Immunization with various vaccines is considered desirable for children with idiopathic nephrotic syndrome (NS) because of their high risk of severe infections. Vaccinations may precipitate relapses of NS, but there is no available data regarding inactivated influenza (flu) virus vaccines. Methods We retrospectively reviewed the medical records of children with NS who had received flu vaccines between 2002 and 2015. The day of flu vaccination was defined as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Evidence and rationale Vaccination with inactivated vaccines should follow the recommended schedule for healthy children, including vaccinating against encapsulated bacteria (especially meningococcal, H. influenza, and pneumococcal). The risk of vaccine-induced relapses has been shown to be low in numerous studies [229][230][231][232]. We recommend annual vaccination against influenza [232][233][234].…”
Section: Vaccinationsmentioning
confidence: 92%
“…Evidence and rationale Vaccination with inactivated vaccines should follow the recommended schedule for healthy children, including vaccinating against encapsulated bacteria (especially meningococcal, H. influenza, and pneumococcal). The risk of vaccine-induced relapses has been shown to be low in numerous studies [229][230][231][232]. We recommend annual vaccination against influenza [232][233][234].…”
Section: Vaccinationsmentioning
confidence: 92%
“…Acute onset of MCD has been described in adults following the influenza vaccine. 19 , 20 Retrospective 21 and, more recently, prospective 22 cohorts of children with nephrotic syndrome have shown a small rate of relapsing disease post-vaccination that is no different from the relapse rate in unvaccinated children. These kinds of comparative analyses have not been reported in adults with nephrotic syndrome.…”
mentioning
confidence: 99%
“…However, the relative risk of a relapse post-vaccine was significantly greater if patients were not in remission at the time of the vaccine. 16 An earlier study from the UK reported significant increases in the relapse rate of idiopathic nephrotic syndrome 12 months after the meningitis C conjugate vaccine. 17 All of these studies are retrospective and have small sample sizes, clearly more research is needed in this area.…”
Section: Discussionmentioning
confidence: 98%